2023
DOI: 10.1126/sciadv.abo7868
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining hypoxia environment of subchondral bone alleviates osteoarthritis progression

Abstract: Abnormal subchondral bone remodeling featured by overactivated osteoclastogenesis leads to articular cartilage degeneration and osteoarthritis (OA) progression, but the mechanism is unclear. We used lymphocyte cytosolic protein 1 ( Lcp1 ) knockout mice to suppress subchondral osteoclasts in a mice OA model with anterior cruciate ligament transection (ACLT), and Lcp1 −/− mice showed decreased bone remodeling in subchondral bone and retarded cartilage d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…OA involves changes in the oxygen environment. Previous studies have revealed that hypoxic levels in the cartilage decreased as OA progressed, which is consistent with our finding of severe cartilage degeneration in the HH‐OA group 19,32 . Notably, chondrocyte clusters, which represent the proliferation and repair stage of OA cartilage, had relatively high hypoxic probe and HIF‐1α expression 33 .…”
Section: Discussionsupporting
confidence: 91%
“…OA involves changes in the oxygen environment. Previous studies have revealed that hypoxic levels in the cartilage decreased as OA progressed, which is consistent with our finding of severe cartilage degeneration in the HH‐OA group 19,32 . Notably, chondrocyte clusters, which represent the proliferation and repair stage of OA cartilage, had relatively high hypoxic probe and HIF‐1α expression 33 .…”
Section: Discussionsupporting
confidence: 91%
“…Osteoarthritis (OA) is a widespread irreversible articular disease marked by articular cartilage deterioration and subsequent osteophytes 1,2 . It affects millions of people worldwide, especially older people over 60 years old 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In the pathogenesis of OA, abnormal osteophytes and bone remodeling of the subchondral bone were essential in determining the severity of the joint injury. [63][64][65] Severe ossification of the subchondral bone in OA rats resulted in the loss of normal mechanical structures (Fig. 7A).…”
Section: Hlc Improved Subchondral Bone Remodeling and Attenuated Cart...mentioning
confidence: 99%